Bipolarolides A–G: Ophiobolin‐Derived Sesterterpenes with Three New Carbon Skeletons from Bipolaris sp. TJ403‐B1. (30th July 2019) - Liu, Mengting; Sun, Weiguang; Shen, Ling; He, Yan; Liu, Junjun; Wang, Jianping; Hu, Zhengxi; Zhang, Yonghui
Abstract: Bipolarolides A–G (1 –7 ), seven novel ophiobolin‐derived sesterterpenes with three new types of skeletons, were characterized from fungus Bipolaris sp. TJ403‐B1. Their structures were determined via spectroscopic analyses, X‐ray crystallography, and quantum chemical 13 C NMR and electronic circular dichroism (ECD) calculations. Compounds 1 and 2 were uniquely defined by a multicyclic caged oxapentacyclo[9.3.0.0 1, 6 .0 5, 9 .1 8, 12 ]pentadecane‐bridged system. Compounds 3 and 4 featured an unprecedented 5‐5‐5‐5‐fused core skeleton, while 3 also contained an unexpected C‐3–C‐14 oxygen bridge to construct the caged architecture. Compounds 5 –7 form a new class of highly modified pentacyclic oxaspiro[4.4]nonane‐containing sesterterpene‐alkaloid hybrids. Their biosynthetic pathways and potential HMG‐CoA reductase inhibitory and antimicrobial activities are also discussed. Abstract : Neue Familienmitglieder : Die Entdeckung von sieben Ophiobolin‐abgeleiteten Sesterterpenen, den Bipolaroliden A–G (1 –7 ), aus dem Pilz Bipolaris sp. TJ403‐B1 fügt der Ophiobolin‐Sesterterpen‐Familie drei neue Klassen hinzu, repräsentiert durch 1, 3 und 6 . Bei einem reversen virtuellen Screening und enzymbasierter In‐vitro‐Validierung erwies sich 1 als HMG‐CoA‐Reduktase‐Inhibitor. Außerdem zeigte 6 eine signifikante antimikrobielle Aktivität gegen Candida albicans .